2009
DOI: 10.1007/s00436-009-1457-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of Cryptosporidium spp. in dairy cattle in Heilongjiang Province, China

Abstract: Few data are available on the molecular characterization of Cryptosporidium spp. in cattle in China. In the present study, a total of 507 fecal specimens from six dairy farms in Heilongjiang Province were examined for Cryptosporidium spp. by light microscopy of concentrates from the formalin-ethyl acetate sedimentation method (for less than 2-month-old calves) or Sheather's floatation method (more than 3-month-old dairy cattle). Twenty-seven post-weaned calves on five farms were positive for Cryptosporidium oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 30 publications
8
24
3
Order By: Relevance
“…Previous surveys of adult calves found that C. andersoni was the predominant species in many countries including Japan, the United States and Canada [9], [45], [46], and this was also the case in China, according to three studies in Heilongjiang, Henan and Shaanxi Provinces [47][49]. In contrast we did not detect C. andersoni in yaks in this study.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous surveys of adult calves found that C. andersoni was the predominant species in many countries including Japan, the United States and Canada [9], [45], [46], and this was also the case in China, according to three studies in Heilongjiang, Henan and Shaanxi Provinces [47][49]. In contrast we did not detect C. andersoni in yaks in this study.…”
Section: Discussioncontrasting
confidence: 63%
“…However, a general trend was observed in many studies: the prevalence of Cryptosporidium declined with increases in age (17,18,31,32). In the present study, a 21.5% infection rate was seen in preweaned dairy calves, which was much higher than the 5.6% (27/485) in postweaned and adult dairy cattle reported in a recent Chinese study (21).…”
Section: Discussioncontrasting
confidence: 45%
“…A previous report on Cryptosporidium in dairy cattle in Heilongjiang Province found that C. andersoni is the most prevalent and the predominant Cryptosporidium spp. in dairy cattle (Liu et al 2009). Because of the existence of host-adapted Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 98%